2017
DOI: 10.1007/s10804-017-9274-9
|View full text |Cite
|
Sign up to set email alerts
|

Extending Working Life: Which Competencies are Crucial in Near-Retirement Age?

Abstract: Nowadays, one of the most important economic and social phenomena is population ageing. Due to the low activity rate of older people, one of the most important challenges is to take various actions involving active ageing, which is supposed to extending working life, and along with it—improve the competencies of older people. The aim of this paper is to evaluate the relevance of different competencies for extending working life, with limiting the analysis for Poland. The paper also assesses the competencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It demonstrates the need to create more university resources. In addition, considering that the population is aging (Wiktorowicz, 2017), the need for these resources is going to grow even more.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It demonstrates the need to create more university resources. In addition, considering that the population is aging (Wiktorowicz, 2017), the need for these resources is going to grow even more.…”
Section: Discussionmentioning
confidence: 99%
“…The population of individuals above the age of 60 will double by 2050 and will experience a threefold increase by 2100. Nowadays, population aging is one of the most important and social phenomena (Wiktorowicz, 2017). Europe has the largest proportion of the world population aged 60 years and over.…”
Section: Introductionmentioning
confidence: 99%
“…The proportion of actively working elderly individuals is increasing in concert with the increased life expectancy. The Organization for Economic Cooperation and Development (OECD) reported that by 2025, 33% of the male population and 38% of the females population working in Europe will be ≥60 years of age (5). According to the Turkish Statistical Institute data, there were approximately 5,891,694 elderly individuals (age, ≥65 years) in 2013, which has increased by 17% over the past five years to reach a population of approximately 6,895,385 in 2017 (6).…”
Section: Introductionmentioning
confidence: 99%